Balancing Tradition and Sustainability: A SWOT Analysis of Tempe SMEs in Sanan, Malang Amidst Environmental Challenges - Wibowo, Andri; Budisaptorini, Anasthasia Triwulan (Indonesian Journal of Advanced Research, 2024)
This study explores the SWOT analysis of the Small and Medium Enterprises (SMEs) specializing in tempe production in Sanan, Malang. The analysis includes the impacts of environmental violations such as air and water pollution. A detailed rating and graphical analysis are provided to illustrate the findings. The study aims to identify the strengths, weaknesses, opportunities, and threats these SMEs face, focusing on their environmental compliance and its effects on their operations and community. The research employs a mixed-method approach, combining qualitative and quantitative data to offer a comprehensive view of the current situation and suggest actionable recommendations.